2015
DOI: 10.1111/dme.12875
|View full text |Cite
|
Sign up to set email alerts
|

National survey of the management of Diabetic Ketoacidosis (DKA) in the UK in 2014

Abstract: 2 Novelty Statementa) In 2013 a revised version of national guidance on the management of DKA was published, however there are no data to show that these recommendations actually work b) This is the largest national survey on the management of DKA c) Most patients developed hypokalaemia and over 25% developed hypoglycaemia. There were also significant issues with care processes d) The management of DKA will need to change to prevent hypokalaemia but will necessitate a shift in where patients are cared for. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
116
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(153 citation statements)
references
References 26 publications
6
116
1
8
Order By: Relevance
“…There were seven (21%) recorded episodes of hypoglycaemia, which is an increase from the audit cycle 1 (10%) but not worse than the national average of 26.7% reported by Dhatariya et al 4 Potassium should be measured and replaced within at least the second hour of admission. Seventeen patients (51%) received potassium replacement within 2 hours of admission (range 2-480 min).…”
Section: Implementation Of the New Guideline Recommendations And Compmentioning
confidence: 64%
See 3 more Smart Citations
“…There were seven (21%) recorded episodes of hypoglycaemia, which is an increase from the audit cycle 1 (10%) but not worse than the national average of 26.7% reported by Dhatariya et al 4 Potassium should be measured and replaced within at least the second hour of admission. Seventeen patients (51%) received potassium replacement within 2 hours of admission (range 2-480 min).…”
Section: Implementation Of the New Guideline Recommendations And Compmentioning
confidence: 64%
“…This is also better than the national average for hypokalaemia (67%) noted at 24 hours of DKA treatment. 4 Ketosis had resolved by 24 hours in >90% of cases across both audit cycles (Table 1). Median time to resolution of ketosis was 12 hours (mean 12.2 hours) compared with a median of 11 hours (mean 11.1 hours) in audit cycle 1.…”
Section: Implementation Of the New Guideline Recommendations And Compmentioning
confidence: 98%
See 2 more Smart Citations
“…While in several previous studies DKA was the presenting feature of type 1 diabetes in up to 30% of cases [11,[21][22][23][24][25], recent data from national surveys in the UK have reported that DKA was the first presentation of type 1 diabetes in adults or adolescents in 3-6% of cases only [26,27]. In addition, the data from the adult survey of over 280 admissions with DKA also showed that mortality was lower than previously reported, with no deaths in the 2016 data, compared with a mortality of 3.9% and 1.8% in UK populations described previously, and 1.7% mortality described recently in a cohort from China [28][29][30].…”
Section: Prevalence Of Dkamentioning
confidence: 88%